Comprehensive analysis of the immune pattern of T cell subsets in chronic myeloid leukemia before and after TKI treatment - Yao, Danlin; Lai, Jing; Lu, Yuhong; Zhong, Jun; Zha, Xianfeng; Huang, Xin; Liu, Lian; Zeng, Xiangbo; Chen, Shaohua; Weng, Jianyu; Du, Xin; Li, Yangqiu; et al. (Frontiers in Immunology, 2023)
Immunological phenotypes and differentiation statuses commonly decide the T cell function and anti-tumor ability. We investigated the immunologic phenotypes (CD38/CD69/HLA-DR/CD28/CD57/BTLA/TIGIT/PD-1) of T subsets (TN, TCM, TEM, and TEMRA) in peripheral blood (PB) and bone marrow (BM) from de novo CML patients (DN-CML), patients who achieved a molecular response (MR) and those who failed to achieve a MR (TKI-F) after tyrosine kinase inhibitor (TKI) treatment using multicolor flow cytometry. The results demonstrated that the percentage of CD38 or HLA-DR positive PB CD8+TN and TCM cells decreased in the DN-CML patients and this was further decreased in TKI-F patients. Meanwhile, the level of PD-1 elevated in CD8+ TEM and TEMRA cells from PB in all groups. Among BM sample, the level of HLA-DR+CD8+TCM cells significantly decreased in all groups and CD8+TEMRA cells from TKI-F patients exhibited increased level of TIGIT and CD8+ tissue-residual T cells (TRM) from DN-CML patients expressed a higher level of PD-1 and TIGIT. Lastly, we found significantly decreased proportion of CD86+ dendritic cells (DCs) and an imbalanced CD80/CD86 in the PB and BM of DN-CML patients, which may impair the activation of T cells. In summary, early differentiated TN and TCM cells from CML patients may remain in an inadequate activation state, particularly for TKI-F patients. And effector T cells (TEM, TEMRA and TRM) may be dysfunctional due to the expression of PD-1 and TIGIT in CML patients. Meanwhile, DCs cells exhibited the impairment of costimulatory molecule expression in DN-CML patients. Those factors may jointly contribute to the immune escape in CML patients.